SJP base material porous structure, manufacturing method and application in hydro-fluctuation belt ecological slope protection
By using the porous structure of SJP substrate and alkali-lowering treatment method on the bank slope of the desolation zone, the problems of erosion and soil erosion caused by waves are solved, and the dual effects of the stability of the bank slope and vegetation growth are achieved.
Patent Information
- Application Number
- CN202411780150.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-28
AI Technical Summary
The existing technology is difficult to effectively solve the problems of erosion and soil erosion caused by waves in the bank slopes of the desolation zone.
The SJP substrate porous structure is adopted, and the SJP organically cured soil slurry is poured into the porous structure made of volcanic stones, gelling materials, etc. through vibration molding. Combined with alkali reduction treatment, it is applied to the ecological slope protection of the desolation zone.
It improves the compressive strength and physical space of the shore slope, enhances water permeability, reduces soil matrix loss, and improves the ecological restoration effect.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ecological restoration of a drawdown zone, relates to a porous structure used in ecological restoration of a drawdown zone, and in particular to a SJP substrate porous structure, a manufacturing method and application in ecological slope protection of a drawdown zone. Background Art
[0002] There are many lakes, rivers and reservoirs in my country, all of which have natural or artificial water level regulation. Based on water level regulation, the water level rises and falls periodically, forming a drawdown zone on the river bank slope. The drawdown zone refers to the area between the highest water level and the lowest water level formed due to periodic water storage caused by natural or artificial regulation. The drawdown zone is a special riverbank zone, which belongs to the transition area between land and water, and is a typical ecological transition zone.
[0003] As the water level rises and falls periodically between the highest and lowest water levels, the geological conditions and ecological environment in the drawdown zone have changed greatly, which has also brought about a series of problems. The main problems include: 1. The periodic rise and fall of the water level has caused erosion on the slopes of the reservoir area, destroyed the soil structure, caused serious soil and water loss in the area, and induced geological disasters such as landslides, collapses and mudslides; 2. The original terrestrial organisms in the reservoir area are difficult to adapt to the harsh environment of water level rise and fall, and gradually die or mutate, biodiversity decreases, the ecosystem structure is fragile, and the function is degraded; 3. The periodic decline and land formation every year has resulted in large areas of bare land and siltation areas with accumulated silt and pollutants, causing serious visual pollution and endangering the living environment.
[0004] In view of the problems caused by the above-mentioned drawdown belt, more and more people are paying attention to the repair and reconstruction of the drawdown belt, especially the protection of the bank slope of the drawdown belt. The existing technology mainly protects the bank slope of the drawdown belt by setting up a slope protection structure on the bank slope and planting vegetation.
[0005] The invention patent with application number 202210943517.9 discloses a method for ecological restoration of the drawdown zone of a reservoir, which includes: drawing the boundary line of the drawdown zone, determining the area of the drawdown zone, and prefabricating a vegetation maintenance structure of the drawdown zone. The vegetation maintenance structure of the drawdown zone includes a water storage device and a ventilation device. The water storage device is set from the top boundary line of the drawdown zone to the bottom boundary line of the drawdown zone, and the ventilation device is set from the bottom boundary line of the drawdown zone to the top boundary line of the drawdown zone. The drawdown zone area is divided into two halves, and waterlogging and drought-resistant plants are planted in the vegetation maintenance structure of the drawdown zone. During the flood season, the plants are not easily flooded and rotten; during the dry season, the plants will not wither and die; in addition, the upstream water diversion control is used to use the upstream water for plant irrigation to prevent the plants from withering during the dry season.
[0006] The invention patent with application number 202311152208.0 discloses a vegetation restoration device suitable for the drawdown zone of a reservoir, including a planting chain belt, which is a pumice unit connected in sequence by connecting parts, and the pumice unit includes a bowl-shaped pumice with an opening facing upward; its production method includes the steps of sintering, slurry making, spraying, drilling, and serial connection; its application uses a planting chain belt to be fixed at one end to the shore in the flood season; the device uses artificial pumice to construct a planting chain belt, and the flood season It floats on water during the dry season and hangs on the cliff or steep slope during the dry season; the weight ratio and connection relationship are set to keep the opening of the bowl-shaped pumice facing upward, avoid plant lodging during the dry season, and make the overall landscape natural and beautiful; multiple pumice units are easy to maintain and reasonably increase the greening restoration area; lightweight metal frames clamp pumice blocks to increase buoyancy and increase strength to resist pulling; seeds are sown directly with mud, without a seedling growth period, and have a high survival rate; the porous structure of the bowl-shaped pumice is conducive to rooting and stem consolidation, inhibits the growth of algae, and has good air permeability for root growth.
[0007] In addition, the invention patent with application number 202311152212.7 discloses a slope protection device for a drawdown zone, including a planting trough, the surface of which is attached with a slurry containing plant seeds, and the planting trough is a porous structure with a bulk density of 1 to 1.1; its production method includes the steps of prefabrication, slurry preparation, slurry soaking, drying, etc.; the device uses a porous structure with a small bulk density to attach the slurry containing plant seeds, which reduces the filling of the medium, is light in weight, free of pulling, and has a low risk of falling off; the multi-pores are conducive to the fixed growth of microorganisms and the firmness of plant roots, and the slurry stabilizes the plant seeds thereon, improves the utilization rate of fertilizer, inhibits water evaporation, enhances water holding capacity, reduces soil erosion, improves strength, and is not easy to weather; the germination of plants adapts to the environment, there is no slow seedling period, and the emergence rate is high; the bottom depression can disperse the water pressure, intercept aquatic plants, epiphytic algae and ground plants, provide a place for organisms, intercept mud and sand to cover the rock slope; the wave-breaking blocks improve the structural strength and buffer the impact and resistance of waves.
[0008] For example, the protection or repair device of the drawdown zone in the above-mentioned invention patent can effectively prevent the erosion of the bank slope, soil erosion, etc. through the device and the vegetation planted on the device. However, waves are also an important factor causing the erosion of the bank slope and soil erosion, and the devices in the above-mentioned invention patents cannot effectively solve the problem of erosion of the bank slope and soil erosion caused by waves. Summary of the invention
[0009] The purpose of the present invention is to solve the problem of bank slope erosion and soil erosion in a drawdown zone caused by waves, and to provide a SJP substrate porous structure, a preparation method and an application in ecological slope protection in a drawdown zone.
[0010] In order to achieve the above-mentioned purpose, the present invention specifically adopts the following technical solutions: A SJP substrate porous structure is made of raw materials containing the following weight percentages: Porous structure 51.5%~56.3%; SJP organic solidified soil paste 43.7%~48.5%; The SJP organic solidified soil slurry is made of raw materials containing the following weight percentages: Viscosity time-varying grouting material 1.2%; Soil 74.8%; Water 24.0%; The porous structure is made of raw materials containing the following weight percentages: Volcanic rocks 64.1-68.2%; Cementitious materials 31.5~35.6%; Water reducing agent 0.1~0.6%.
[0011] Further, it is made from raw materials containing the following weight percentages: porous structure 54.7%; SJP organically stabilized soil paste 45.3%; The SJP organic solidified soil slurry is made of raw materials containing the following weight percentages: Viscosity time-varying grouting material 1.2%; Soil 74.8%; Water 24.0%; The porous structure is made of raw materials containing the following weight percentages: volcanic rock 66.8%; cementitious materials 32.8%; Water reducing agent 0.4%.
[0012] Further, the gelling material is made of raw materials comprising the following weight percentages: Portland cement 50.2~54.1%; Fly ash 10.1~14.5%; Water 32.3~37.9%.
[0013] Further, the silicate cement is silicate cement with a strength grade of P.O42.5, and the fly ash is secondary fly ash; Among them, the loss on ignition of silicate cement is 0.97, and the weight percentage of each oxide in silicate cement is: SiO220.38~22.35%; Fe2O34.47~4.82%; Al2O35.23~5.89%; CaO61.01~63.19%; MgO2.05~2.96%; SO31.55~1.73%; NaO1.02~1.10%.
[0014] A method for making the above-mentioned SJP substrate porous structure, the specific steps are: (1) Preparation of porous structure; (2) Prepare SJP organic solidified soil slurry; (3) The SJP organic solidified soil slurry is poured into the porous structure by vibration molding to obtain the SJP substrate porous structure.
[0015] Furthermore, the preparation of the porous structure includes the following steps: (1-1) Pour all the volcanic rocks into a mixer and add 45-55% water, stirring to pre-wet the volcanic rocks; (1-2) Add 60-80% of cementitious material and 60-80% of water reducing agent into the mixer and stir until the volcanic rock is completely covered by the adhesive material to form a shell; (1-3) Add the remaining water to the blender and continue blending until the shell becomes thinner and evenly coated; (1-4) Slowly add the remaining cementitious material and water reducing agent into the mixer while stirring; (1-5) After the mixing is completed, the mixed material is poured into a mold and vibrated, and then molded to obtain a porous structure.
[0016] Furthermore, the porous structure of the SJP substrate obtained in step (3) is subjected to an alkali reduction treatment, and the specific treatment method is as follows: The porous structure of the SJP substrate was immersed in a 2% oxalic acid solution or a 7% FeSO4 solution.
[0017] An application of the above-mentioned SJP substrate porous structure in ecological slope protection in a drawdown zone.
[0018] The beneficial effects of the present invention are as follows: 1. In the present invention, the SJP organic solidified soil slurry is poured into a porous structure made of volcanic rock, cementitious materials, etc. by vibration molding to obtain an SJP substrate porous structure; the SJP substrate porous structure not only has high strength, but also has good vegetation space and good water permeability; according to experiments, under the reinforcement of the SJP organic material, the soil particles are agglomerated together, which can resist the infiltration water flow formed inside the porous structure, making it difficult for the deep soil fine particles inside the porous structure to migrate, and the vegetation soil retention effect is better, thereby better solving the problem of soil matrix loss in the early stage of ecological restoration of the water-drawing zone when the vegetation roots have not grown up, retaining the soil matrix and vegetation space for subsequent plant growth, and bringing new results to the restoration of the water-drawing zone.
[0019] 2. In the present invention, the porous structure of the SJP substrate is treated with alkali reduction. When the porous material after the alkali reduction treatment is used in the ecological slope protection of the drawdown zone, the precipitation of calcium hydroxide in the porous material with the migration of water is reduced, the salinization of the soil is reduced, and its impact on the environment is greatly reduced; soaking in oxalic acid solution will produce a layer of calcium oxalate on the surface of the porous material, which prevents the alkaline infiltration of the porous skeleton, and does not affect the compressive properties of the porous material, and the compressive properties of the porous material will not be affected by the alkali reduction treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a schematic diagram of a porous structure in an interlocking state in the present invention; Figure 2 is a schematic diagram of the results of the compression test of the present invention; Among them, Figure A shows the compressive strength under different water-cement ratios, Figure B shows the compressive strength under different aggregate particle sizes, and Figure C shows the compressive strength under different cementitious material dosages; Figure 3 It is a schematic diagram of the results of the pore characteristics test of the present invention; Among them, Figure A shows the porosity change under different water-cement ratios, Figure B shows the porosity change under different aggregate particle sizes, and Figure C shows the porosity change under different cementitious material dosages; Figure 4 Schematic diagram of the relationship between effective porosity and total porosity in the present invention; Figure 5 It is a schematic diagram of the result of the water permeability test of the present invention; Among them, Figure A shows the change of water permeability coefficient under different water-cement ratios, Figure B shows the change of water permeability coefficient under different aggregate particle sizes, and Figure C shows the change of water permeability coefficient under different cementitious material dosages; Figure 6 It is a schematic diagram of the relationship between the effective porosity and the water permeability coefficient in the present invention; Figure 7Schematic diagram of pH and compressive strength of the porous structure of the SJP substrate after alkali reduction treatment in the present invention; Figure A shows the Ph of the skeleton after being soaked in different acid solutions, and Figure B shows the compressive strength of the skeleton after being soaked in different acid solutions; Figure 8 It is a schematic diagram of the changes in pH and conductivity of the packaged soil at different curing ages in the present invention; Among them, Figure A shows the change of soil pH after alkalinity reduction, and Figure B shows the change of soil conductivity after alkalinity reduction; Fig. 9 It is a schematic diagram of the vegetation test process in the present invention; Fig.10 It is a schematic diagram of effective wave height during the application test of the present invention in ecological slope protection in a drawdown zone; Among them, Figure A is a histogram of significant wave height distribution, and Figure B is a distribution diagram of significant wave height daily changes; Fig.11 It is a schematic diagram of soil particle distribution in the test area of the present invention; Among them, Figure A is the original soil particle distribution curve, Figure B is the surface soil particle distribution curve of the test area, Figure C is the 0-5cm soil particle distribution curve of the test area, and Figure D is the 5-10cm soil particle distribution curve of the test area; Fig.12 It is a schematic diagram of soil particle distribution in the control area of the present invention; Among them, 165DS0-5: 0~5cm soil in the upper part of the 165m frame, 165DZ0-5: 0~5cm soil in the middle part of the 165m frame; 165DX0-5: 0~5cm soil in the lower part of the 165m frame, and so on; Fig.13 It is a schematic diagram of the analysis of soil particle composition at different parts of the control area in the present invention; Among them, Figure A is the soil particle distribution curve of 165DS0-5, Figure A is the soil particle distribution curve of 165DS5-10, Figure A is the soil particle distribution curve of 165DZ0-5, Figure A is the soil particle distribution curve of 165DZ5-10, Figure A is the soil particle distribution curve of 165DX0-5, and Figure A is the soil particle distribution curve of 165DX5-10. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0022] Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.
[0023] Example 1 This embodiment provides a SJP substrate porous structure, which is made of raw materials containing the following weight percentages: porous structure 52.4%; SJP organically stabilized soil paste 47.6%; The SJP organic solidified soil slurry is made of raw materials containing the following weight percentages: Viscosity time-varying grouting material 1.2%; Soil 74.8%; Water 24.0%; The porous structure is made of raw materials containing the following weight percentages: volcanic rock 64.5%; Cementitious materials 35%; Water reducing agent 0.5%.
[0024] The porous structure consists of lightweight aggregate volcanic rock, cementitious material, water reducer and water, and is prepared by the shell making method. During the mixing process, the cementitious material dosage is small, and the aggregates are mainly in a chain state (such as Figure 1 As shown), it has excellent pore structure and vegetation performance.
[0025] The aggregate size of the volcanic rock is 18 mm and the apparent density is 1642.6 kg / m 3 , bulk density is 691.7 kg / m 3 , the void ratio is 0.56% and the aggregate water absorption rate is 7.6%.
[0026] The gelling material is made of raw materials containing the following weight percentages: Portland cement 53.2%; Fly ash 10.5%; Water 36.3%.
[0027] Among them, the silicate cement is silicate cement with a strength grade of P.O42.5, and the fly ash is secondary fly ash; the loss on ignition of the silicate cement is 0.97, and the weight percentage of each oxide in the silicate cement is: SiO2 21.63%; Fe2O34.71%; Al2O35.84%; CaO 63.02%; MgO2.13%; SO31.59%; NaO1.08%.
[0028] The initial setting time of silicate cement is 75 minutes, the final setting time is 154 minutes, the flexural strength at 3 days is 6.45 MPa, the flexural strength at 28 days is 8.53 MPa, the compressive strength at 3 days is 27.82 MPa, and the compressive strength at 28 days is 54.21 MPa.
[0029] The bulk density of the water reducer is 526 kg / m 3 , pH value is 7.3, and water content is 2.3.
[0030] The gray-water ratio is 0.377.
[0031] A method for making the above-mentioned SJP substrate porous structure, the specific steps are: (1) Preparation of porous structure; (2) Prepare SJP organic solidified soil slurry; (3) The SJP organic solidified soil slurry is poured into the porous structure by vibration molding to obtain the SJP substrate porous structure. In addition, the SJP substrate porous structure can also be subjected to alkali reduction treatment, and the specific treatment method is: soaking the SJP substrate porous structure with a 2% oxalic acid solution.
[0032] The preparation of the porous structure includes the following steps: (1-1) Pour all the volcanic rocks into a mixer and add 46% water (the water here is not the water in the volcanic rocks, cementitious materials and water reducing agent mentioned above; the amount of water here can be selected according to the actual situation, the same below), and stir for 1 minute to pre-wet the volcanic rocks; (1-2) Add 62% of cementitious material and 65% of water reducing agent into a mixer and stir for 3 minutes until the volcanic rock is completely covered by the adhesive material to form a shell; (1-3) Add the remaining water to the blender and continue blending for 2 minutes to make the shell thinner and more evenly coated; (1-4) Slowly add the remaining cementitious material and water reducing agent into the mixer, stirring while adding for 2 minutes; (1-5) After the mixing is completed, the mixed material is poured into a mold and vibrated, and then molded to obtain a porous structure.
[0033] Example 2 This embodiment provides a SJP substrate porous structure, which is made of raw materials containing the following weight percentages: porous structure 53.7%; SJP organically stabilized soil paste 46.3%; The SJP organic solidified soil slurry is made of raw materials containing the following weight percentages: Viscosity time-varying grouting material 1.2%; Soil 74.8%; Water 24.0%; The porous structure is made of raw materials containing the following weight percentages: volcanic rock 64.9%; cementitious materials 34.8%; Water reducing agent 0.3%.
[0034] The aggregate size of the volcanic rock is 22.3 mm and the apparent density is 1659.4 kg / m 3 , bulk density is 706.4kg / m 3 , the void ratio is 0.56% and the aggregate water absorption rate is 7.6%.
[0035] The gelling material is made of raw materials containing the following weight percentages: Portland cement 53.3%; Fly ash 12.3%; Water 34.4%.
[0036] Among them, the silicate cement is silicate cement with a strength grade of P.O42.5, and the fly ash is secondary fly ash; the loss on ignition of the silicate cement is 0.97, and the weight percentage of each oxide in the silicate cement is: SiO2 21.59%; Fe2O34.61%; Al2O35.37%; CaO 62.84%; MgO2.84%; SO31.70%; NaO1.05%.
[0037] The initial setting time of silicate cement is 103min, the final setting time is 172min, the flexural strength at 3 days is 6.53Mpa, the flexural strength at 28 days is 8.64Mpa, the compressive strength at 3 days is 28.94Mpa, and the compressive strength at 28 days is 56.21Mpa.
[0038] The bulk density of the water reducer is 567 kg / m 3 , pH value is 7.5, and water content is 1.8.
[0039] The gray-water ratio is 0.317.
[0040] A method for making the above-mentioned SJP substrate porous structure, the specific steps are: (1) Preparation of porous structure; (2) Prepare SJP organic solidified soil slurry; (3) The SJP organic solidified soil slurry is poured into the porous structure by vibration molding to obtain the SJP substrate porous structure. In addition, the SJP substrate porous structure can also be treated by reducing alkali, and the specific treatment method is: soaking the SJP substrate porous structure in a 7% FeSO4 solution.
[0041] The preparation of the porous structure includes the following steps: (1-1) Pour all the volcanic rocks into a blender and add 52% water. Stir for 2 minutes to pre-wet the volcanic rocks. (1-2) Add 75% of cementitious material and 62% of water reducing agent into a mixer and stir for 2 minutes until the volcanic rock is completely covered by the adhesive material to form a shell; (1-3) Add the remaining water to the blender and continue blending for 3 minutes to make the shell thinner and more evenly coated; (1-4) Slowly add the remaining cementitious material and water reducing agent into the mixer, stirring while adding for 1 minute; (1-5) After the mixing is completed, the mixed material is poured into a mold and vibrated, and then molded to obtain a porous structure.
[0042] Example 3 This embodiment provides a SJP substrate porous structure, which is made of raw materials containing the following weight percentages: porous structure 54.1%; SJP organically stabilized soil paste 45.9%; The SJP organic solidified soil slurry is made of raw materials containing the following weight percentages: Viscosity time-varying grouting material 1.2%; Soil 74.8%; Water 24.0%; The porous structure is made of raw materials containing the following weight percentages: volcanic rock 66.9%; cementitious materials 32.9%; Water reducing agent 0.2%.
[0043] The aggregate size of the volcanic rock is 30.4 mm and the apparent density is 1702.4 kg / m 3 , bulk density is 742.4 kg / m 3 , the void ratio is 0.57% and the aggregate water absorption rate is 7.7%.
[0044] The gelling material is made of raw materials containing the following weight percentages: Portland cement 52.2%; Fly ash 14.1%; Water 33.7%.
[0045] Among them, the silicate cement is silicate cement with a strength grade of P.O42.5, and the fly ash is secondary fly ash; the loss on ignition of the silicate cement is 0.97, and the weight percentage of each oxide in the silicate cement is: SiO2 22.17%; Fe2O34.75%; Al2O35.76%; CaO 61.78%; MgO2.82%; SO31.64%; NaO1.08%.
[0046] The initial setting time of silicate cement is 89 minutes, the final setting time is 158 minutes, the flexural strength at 3 days is 6.81 MPa, the flexural strength at 28 days is 8.73 MPa, the compressive strength at 3 days is 29.24 MPa, and the compressive strength at 28 days is 55.42 MPa.
[0047] The bulk density of the water reducer is 672 kg / m 3 , pH value is 8.5, and water content is 2.4.
[0048] The gray-water ratio is 0.364.
[0049] A method for making the above-mentioned SJP substrate porous structure, the specific steps are: (1) Preparation of porous structure; (2) Prepare SJP organic solidified soil slurry; (3) The SJP organic solidified soil slurry is poured into the porous structure by vibration molding to obtain the SJP substrate porous structure. In addition, the SJP substrate porous structure can also be treated with alkali reduction, and the specific treatment method is: soaking the SJP substrate porous structure with a 2% oxalic acid solution or a 7% FeSO4 solution.
[0050] The preparation of the porous structure includes the following steps: (1-1) Pour all the volcanic rocks into a blender and add 49% water. Stir for 2 minutes to pre-wet the volcanic rocks. (1-2) Add 67% of cementitious material and 76% of water reducing agent into a mixer and stir for 3 minutes until the volcanic rock is completely covered by the adhesive material to form a shell; (1-3) Add the remaining water to the blender and continue blending for 3 minutes to make the shell thinner and more evenly coated; (1-4) Slowly add the remaining cementitious material and water reducing agent into the mixer, stirring while adding for 2 minutes; (1-5) After the mixing is completed, the mixed material is poured into a mold and vibrated, and then molded to obtain a porous structure.
[0051] Example 4 This embodiment provides a SJP substrate porous structure, which is made of raw materials containing the following weight percentages: porous structure 55.8%; SJP organically stabilized soil paste 44.2%; The SJP organic solidified soil slurry is made of raw materials containing the following weight percentages: Viscosity time-varying grouting material 1.2%; Soil 74.8%; Water 24.0%; The porous structure is made of raw materials containing the following weight percentages: volcanic rock 65.9%; cementitious materials 33.7%; Water reducing agent 0.4%.
[0052] The aggregate size of the volcanic rock is 27.4 mm and the apparent density is 1652.7 kg / m 3 , bulk density is 724.5kg / m 3 , the void ratio is 0.58% and the aggregate water absorption rate is 7.8%.
[0053] The gelling material is made of raw materials containing the following weight percentages: Portland cement 51.9%; Fly ash 11.7%; Water 36.4%.
[0054] Among them, the silicate cement is silicate cement with a strength grade of P.O42.5, and the fly ash is secondary fly ash; the loss on ignition of the silicate cement is 0.97, and the weight percentage of each oxide in the silicate cement is: SiO2 22.27%; Fe2O34.52%; Al2O35.49%; CaO 62.53%; MgO2.58%; SO31.58%; NaO1.03%.
[0055] The initial setting time of silicate cement is 96 minutes, the final setting time is 164 minutes, the flexural strength at 3 days is 6.78 MPa, the flexural strength at 28 days is 8.81 MPa, the compressive strength at 3 days is 28.61 MPa, and the compressive strength at 28 days is 53.99 MPa.
[0056] The bulk density of the water reducer is 649 kg / m 3 , pH value is 8.2, and water content is 2.8.
[0057] The gray-water ratio is 0.355.
[0058] A method for making the above-mentioned SJP substrate porous structure, the specific steps are: (1) Preparation of porous structure; (2) Prepare SJP organic solidified soil slurry; (3) The SJP organic solidified soil slurry is poured into the porous structure by vibration molding to obtain the SJP substrate porous structure. In addition, the SJP substrate porous structure can also be treated with alkali reduction, and the specific treatment method is: soaking the SJP substrate porous structure with a 2% oxalic acid solution or a 7% FeSO4 solution.
[0059] The preparation of the porous structure includes the following steps: (1-1) Pour all the volcanic rocks into a blender and add 53% water. Stir for 1 to 2 minutes to pre-wet the volcanic rocks. (1-2) Add 75% of cementitious material and 72% of water reducing agent into a mixer and stir for 3 minutes until the volcanic rock is completely covered by the adhesive material to form a shell; (1-3) Add the remaining water to the blender and continue blending for 2 minutes to make the shell thinner and more evenly coated; (1-4) Slowly add the remaining cementitious material and water reducing agent into the mixer, stirring while adding for 1 minute; (1-5) After the mixing is completed, the mixed material is poured into a mold and vibrated, and then molded to obtain a porous structure.
[0060] Example 5 Application of a porous structure of SJP substrate in ecological slope protection in a drawdown zone.
[0061] The above-mentioned SJP substrate porous structure is covered on the slope protection of the drawdown zone, and the surface of the SJP substrate porous structure is covered with about 3 cm of solidified soil, and Bermuda grass, a dominant plant in the upper drawdown zone, is planted.
[0062] Test example (compressive strength of porous structure) A small mixer was used to prepare multiple groups of porous structures with a size of 100mm*100mm*100mm. The multiple groups of porous structures can be divided into porous structure combinations with different water-cement ratios, porous structure combinations with different aggregate particle sizes, and porous structure combinations with different cementitious material dosages. The above-mentioned porous structures were molded and demoulded within 24 hours to obtain test pieces. The test pieces were immersed in water and cured to the corresponding age before the compression test. The compressive strength test method was referred to the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". The tester was a microcomputer-controlled electro-hydraulic servo pressure testing machine, model: YAW-600D.
[0063] The specific steps of the test are: (1) After the specimens have been cured for 28 days, the compressive surface is sealed with M5 mortar to ensure that the compressive surface is flat. The compressive strength test is carried out 2 days after the sealing treatment. (2) Align the smooth surface of the specimen with the upper and lower pressure plates of the compression machine. After the center is symmetrical, operate the compression machine to lift and lower so that the upper and lower pressure plates are in uniform contact with the specimen; (3) Turn on the compression machine and load at a loading rate of 0.1 MPa / s until the specimen is damaged, then stop loading.
[0064] Calculate the compressive strength of the specimen using the following formula:
[0065] In the formula, Indicates the compressive strength of standard cubic specimen (MPa), represents the specimen failure load (N), Indicates the compressive area of the specimen (mm 2 ).
[0066] Test results: like Figure 2 As shown in A, the compressive strength of the porous structure gradually increases with the extension of the curing age. Under the same curing age, when the water-cement ratio increases from 0.25 to 0.35, the compressive strength gradually increases. When the water-cement ratio is 0.35, the 28-day compressive strength reaches a maximum value of 1.1 MPa. When the water-cement ratio continues to increase, the compressive strength decreases instead. According to research, this is mainly because when the water-cement ratio is small, the slurry wraps the aggregate unevenly and the slurry is dry, resulting in incomplete hydration; when the water-cement ratio is 0.35, the aggregate surface is uniformly wrapped with a porous structure with high overall stability, while when the water-cement ratio is greater than 0.35, the slurry is too thin and the fluidity is high, resulting in a thinner thickness of the aggregate wrapping, and the slurry will be deposited at the bottom of the test block due to its own gravity, resulting in a thicker thickness at the bottom and thinner thickness at the top, and the overall compressive strength of the test block is reduced. Therefore, a water-cement ratio of about 0.35 is more suitable.
[0067] like Figure 2As shown in Figure B, at a fixed water-cement ratio (0.35) and a fixed unit cementitious slurry volume (20%), the smaller the aggregate size, the higher the compressive strength of the porous component. This is because when the aggregate size is smaller, there will be more contact points between the coarse aggregates, the porous structure will be closer to solid, the pores will be fine, and the vegetation slurry will be difficult to penetrate. Considering the two factors of compressive strength and vegetation slurry penetration, it is considered that the selection of aggregates of about 2 cm is more appropriate.
[0068] like Figure 2 As shown in C, with the increase of gelled slurry, the compressive strength of the porous skeleton increases, but too much slurry will cause the slurry to sink, resulting in the upper and lower sides of the skeleton being disconnected and the water permeability being poor.
[0069] Test example (pore characteristics of porous structure) The porous structure is a porous structure composed of volcanic rocks, cementitious materials and water reducing agents. Different from ordinary concrete structures, it has large pores and good connectivity. The pore characteristics are closely related to the permeability of the porous structure, vegetation space and other functions.
[0070] The specific steps of the test are: (1) Soak the sample in water and keep it cured until it is saturated with water. Take it out 1 day in advance and put it on a hydrostatic balance to weigh the mass m1.
[0071] (2) Then place it in the air for 24 hours and weigh it, the natural mass is m2.
[0072] (3) On the day of aging, place the sample in a drying oven (60℃, 24h), dry it to constant weight, and weigh its mass m3.
[0073] The total porosity calculation formula is:
[0074] The calculation formula of connected porosity is:
[0075] In the formula, Indicates the density of water (g / cm 3 ), Indicates the displacement volume (cm 3 ), represents the mass in water (g), Indicates natural weight (g), Indicates the oven-dried constant weight (g).
[0076] Test results: like Figure 3As shown in the figure, in the single factor test of water-cement ratio and aggregate particle size, there is no significant difference in porosity and effective porosity between different water-cement ratios and different aggregate particle sizes. The total porosity is in the range of 40.2-45.3%, and the effective porosity is about 35.6-39.5%, with a difference of about 6%, indicating that there are about 6% closed pores in the porous structure, which cannot be used for subsequent plant growth and are invalid pores.
[0077] At different cementitious volume dosages, the porosity of the two parts varies greatly, indicating that the cementitious slurry dosage is the most critical influencing factor controlling the porosity of the porous structure. With the increase of cementitious slurry dosage, the porosity and effective porosity of the porous structure per unit volume are significantly reduced. The total porosity decreases from 46.3% to 33.1%, while the effective porosity decreases from 41.3% to 26.8%. Both porosities are higher than the theoretically calculated porosity. This is because there is a certain amount of slurry loss in the process of making the porous structure, and the loss is about 5~7%.
[0078] like Figure 4 As shown in the figure, the porosity and effective porosity of the porous structure prepared by the single factor test under different water-cement ratios, aggregate particle sizes, and cementitious paste dosages were measured. According to the previous test results, the porosity and effective porosity of the porous structure were statistically analyzed, and it was found that there was a good quadratic function relationship between the two, R 2 =0.9183.
[0079] Test example (water permeability coefficient of porous structure) The water permeability coefficient is an indicator to measure the water permeability of porous structures. The porous structure has continuous voids and semi-continuous voids inside, which has good water permeability. The porous structure has coarse aggregates and good drainage capacity. This test example uses a laboratory-made constant head instrument to measure the water permeability coefficient of its test block in accordance with "Water Permeability of Macroporous Concrete and Its Determination Method".
[0080] Test method: (1) Cylindrical (110 mm in diameter, 150 mm in height) porous structures with different mix ratio designs were prepared and placed in water for curing for 28 days. The specimens were then immersed in water for 24 hours to achieve saturation. (2) Place the specimens that have reached the required age into a PVC pipe, open the water supply valve to allow water to enter the container, and adjust the water inlet to keep a certain water level (about 150 mm) in the prism sealing device. After the amount of water flowing out of the overflow port of the prism sealing device stabilizes, use a measuring container to collect water from the outlet and record the amount of water flowing out in 90 s (Q). Measure three times and take the average value.
[0081] (3) Use a steel ruler to measure the difference (H) between the water level in the prism seal and the water level on the upper surface of the test piece, accurate to 1 mm. Use a thermometer to measure the temperature of the water in the prism seal during the test (T), accurate to 1°C.
[0082] The formula for calculating the water permeability coefficient is:
[0083] in, Indicates the water permeability coefficient of the test piece at water temperature T℃ (mm / s), Indicates the amount of water flowing out in t seconds (mm 3 ), Indicates the thickness of the specimen (mm 2 ), Indicates the upper surface area (mm 2 ), Indicates the water level difference (s).
[0084] The test result is based on the average value of the three test pieces, and the calculation is accurate to 1.0*10 -2 mm / s.
[0085] This test example uses 15℃ water temperature as the standard temperature. The water permeability coefficient at the standard temperature should be calculated according to the formula:
[0086] in, Indicates the water permeability coefficient of the specimen at standard temperature (mm / s), Indicates the dynamic viscosity of water at T℃ (kPa·s), Indicates the dynamic viscosity of water at 15°C (kPa·s), Represents the dynamic viscosity ratio of water.
[0087] Test results: like Figure 5 As shown in the figure, as the water-cement ratio increases, the water permeability coefficient increases slightly. This is because as the water-cement ratio increases, the fluidity of the slurry increases, which leads to a thinner wrapping thickness of the slurry on the aggregate and an increase in the permeable area per unit thickness. For different aggregate particle sizes, the water permeability coefficient is positively correlated with the particle size. When the aggregate increases, the pores formed by the accumulation are also larger, so the water permeability coefficient also increases accordingly. As for the effect of the cementitious slurry dosage on the water permeability coefficient, it can be seen that as the cementitious slurry in the unit volume structure increases, the water permeability coefficient decreases significantly. When the slurry volume dosage is 15~25%, the water permeability coefficient ranges from 2.56~3.55 cm / s. When the dosage is 30%, the water permeability coefficient is 0.03 cm / s, and the bottom of the porous structure is sealed by sedimentation. At this time, the porous structure has lost its permeability. In summary, the volume dosage of cementitious slurry should be below 25%.
[0088] like Figure 6 As shown in Figure 2, when the cementitious content is less than 25%, the effective porosity and water permeability coefficient show a strong correlation, and the correlation coefficient R 2 As high as 0.9461. It can be seen that the water permeability coefficient gradually increases with the increase of effective porosity, that is, the effective porosity is particularly important for the water permeability of porous structures. Therefore, when preparing porous structures, it is particularly important to choose the appropriate amount of cementitious slurry. Combined with the above porosity research, in order to make the porous structure have enough vegetation space and good water permeability, the volume content of cementitious slurry should be controlled below 25%, which is consistent with the previous conclusion.
[0089] Test example (alkali reduction treatment of porous structure of SJP substrate) Test method: Multiple groups of SJP substrate porous structures prepared by the above method were immersed in 2% oxalic acid solution and 7% FeSO4 solution, respectively. The pH after immersion for 1, 3, 5, and 7 days was tested, and the alkalinity-reducing effects of the two were compared.
[0090] pH test method: The porous structure of the SJP substrate after the alkali reduction treatment was carefully washed to remove the residual acid solution, and was immersed in 3L of clean water with a sealed cover for 24 hours until the pH remained unchanged. The pH of the immersion solution was measured with a pH meter as a characterization pH of the effect of the porous structure of the SJP substrate on the alkalinity of the soil.
[0091] Test results: from Figure 7 A shows that soaking in FeSO4 solution has a slight advantage, but oxalic acid can also achieve the effect of reducing alkali. And from the principle of reducing alkali, soaking in FeSO4 solution belongs to sulfate erosion. The FeSO4 soaking used in the experiment will hydrolyze Fe 2+ It reacts with the alkaline substance Ca(OH)2 generated by cement hydration to generate Fe(OH)2 and CaSO4. 2+ will react with the ionized OH - Combined, thus generating a small amount of Fe(OH)2 precipitation (easy to oxidize), reducing OH - concentration to achieve the purpose of reducing the alkalinity of the specimen. However, this method will reduce the compressive strength of porous components (such as Figure 7 B), the compressive strength (7 d) and compressive strength (28 d) of the skeleton after the alkali reduction method decreased by about 22.7% and 25.6%, respectively; while soaking in oxalic acid solution would produce a layer of calcium oxalate on the surface, which prevented the alkaline infiltration of the porous skeleton and did not have a significant impact on the compressive strength.
[0092] According to this test example, it is more reasonable to use oxalic acid solution for alkalinity reduction treatment. In addition, in addition to the immersion method in this test example, the soil packaging method can also be used for measurement. In this test example, the soil packaging method will not be described in detail.
[0093] Test example (Soil pH and conductivity of porous structure of SJP substrate) Test method: The porous structure of the SJP substrate with different curing ages (7d / 28d) was soaked in 2% oxalic acid for 3 days to reduce the alkali. The acid on the surface was washed off after soaking, and the existing soil packaging method was used to determine the pH and conductivity of the soil at different packaging times to scientifically evaluate its alkali reduction effect.
[0094] Test results: like Figure 8 As shown in A, after the 7-day SJP substrate porous structure was de-alkalied, the pH of the soil wrapped showed a slight increase trend with the wrapping time, ranging from 8.02 to 8.45, while the pH of the soil wrapped by the SJP substrate porous structure after curing for 28 days was 7.97 to 8.12. It can be seen that oxalic acid soaking can reduce the pH of the wrapped soil, making the soil alkalinity lower and no longer strong alkalinity. Cynodon dactylon has a certain alkalinity tolerance, and the plant can grow normally in the soil with a pH of 8.7; and the soil pH after de-alkali did not reach this extreme value, indicating that the soil after de-alkali is more suitable for the growth of Cynodon dactylon in the drawdown zone.
[0095] like Figure 8 As shown in Figure B, after oxalic acid treatment, the conductivity of the soil was 112.6~142.3μs / cm, while the conductivity at 7d / 28d of curing was 215~230μs / cm and 135.8~190μs / cm respectively. It can be seen that oxalic acid immersion will also reduce the conductivity of the wrapped soil, and the conductivity is significantly positively correlated with the salt content in the soil, indicating that the salt content in the soil is also significantly reduced.
[0096] Test example (vegetation test on porous structure of SJP substrate) Test method: The porous structure of the SJP substrate was covered on the drawdown zone, and the surface of the porous structure of the SJP substrate was covered with about 3 cm of solidified soil, and the dominant plant of the upper drawdown zone, Bermuda grass, was planted. The planting density of Bermuda grass was 25 g / m 2 , and conduct tests to verify its vegetation performance.
[0097] Test results: like Fig. 9As shown in the figure, the porous structure of the SJP substrate without alkalinity reduction will cause the soil to become salinized and make it difficult for bermudagrass to grow. After the porous structure of the SJP substrate was cured for 28 days and then covered with soil for sowing, although bermudagrass could grow, the rhizomes and leaves of bermudagrass were relatively thin, the growth was not good, and there was a tendency to yellow and wither. After the porous structure of the SJP substrate was cured to the corresponding age (7 d / 28 d), 2% oxalic acid was used for alkalinity reduction treatment. The planting effect of bermudagrass was better, and the bermudagrass that was alkalinity reduced after 7 days of curing showed no signs of yellowing. At this time, the pH of the soil was 8.31 and the conductivity was 120.3 μs / cm. In summary, the porous structure of the SJP substrate can be cured for 7 days and then soaked in 2% oxalic acid for 3 days for alkalinity reduction treatment, and then covered with soil for planting. This alkalinity reduction method can not only shorten the use time of the structure, but also achieve better planting effects.
[0098] Test example (Application of porous structure of SJP substrate in ecological slope protection of drawdown zone) 1. Preparation of porous structure of SJP substrate 1. Selection of test area and control area: The field test area is located in the eastern part of the annular drawdown zone of Baidicheng Scenic Area, with an elevation distribution range of 145~175m and a slope of about 45~53°. It is a lattice anchor spray-mixing area. The slope has not been ecologically restored, and the vegetation coverage rate is low. The lattice beam is a diamond-shaped knot with a side length of about 2.5m and a beam width of about 15cm.
[0099] The control area is located below the parking lot in the southwest of Baidicheng Scenic Area. The slope has been repaired with a common porous structure formed by gravel soil covering. The vegetation coverage gradually decreases from the top to the bottom of the slope, and the repair effect is poor. The slope is about 2100m away from the test area, with an elevation distribution of 165~175m. The frame structure is a square with a side length of about 2.5m and a beam width of about 15cm.
[0100] 2. Preparation of porous structure of SJP substrate and alkali reduction: Volcanic rock, cementitious material and water reducer are mixed according to the mix ratio and preparation process to obtain a porous structure; after stirring and forming, it is covered with plastic film and cured for 7 days, and water is sprayed during the curing period to keep its surface moist; after curing for 7 days, it is immersed in a 2% oxalic acid solution for 3 days; then the viscosity time-varying grouting material (i.e. SJP material, developed and disclosed by the team of Professor Pei Xiangjun of Chengdu University of Technology) is fully mixed with the local soil with a water-soil ratio of 0.35, and after it is fully mixed, it is poured into the porous structure, and the slurry is made to completely fill the porous structure by vibration compaction, and then it is allowed to stand to form, so as to obtain the SJP substrate porous structure.
[0101] 3. Installation of SJP substrate porous structure: The bottom of the formed SJP substrate porous structure was coated with cement mortar and installed in the lattice panel area of the slope of the test area from bottom to top. Subsequent operations were carried out after the cement mortar solidified.
[0102] 4. Surface grass seed mixed spraying: Mix the soil, viscosity time-varying grouting material (SJP material) and grass seeds thoroughly (SJP dosage: 1.2%, grass seed density: 25-30g / m 2 ), forming slurry grass seeds; then spray the slurry grass seeds on the slope of the porous planting structure (i.e., the porous structure with SJP substrate installed), with a spraying thickness of about 2~3cm. Finally, cut the bermudagrass into diameter sections with a length of about 5~10cm, insert it into the surface layer and compact it.
[0103] 5. Maintenance and treatment: After the spray seeding is completed, use an atomizing nozzle to spray water once in the morning, noon and evening every day to minimize the strong runoff erosion formed on the surface due to spraying water to prevent the soil and grass seeds from being carried away.
[0104] 2. Wave Data Collection The RBR pressure-type self-contained wave tide meter produced by Canada RBR Company was used to obtain wave characteristics. The wave meter was deployed in the field test area, located behind the Baidicheng Wharf and the main channel. The water depth at the instrument deployment point was about 1.5m, the sampling interval was set to 5min, the pulse frequency was 16Hz, and the original data such as pressure, water depth and tide level were obtained after continuous observation for 24h. The surface wave spectrum was obtained by using the pressure change of the high-resolution pressure sensor to obtain the wave-related characteristic parameters.
[0105] 3. Soil Data Collection The layered excavation method was used for sampling, and the surface, 0~5cm and 5~10cm soils from the exposed area (upper part of the frame) of the field test were analyzed. The control area was sampled using the same method (sampling altitude 165m), and soils from different parts and depths (surface, 0~5cm, 5~10cm) were taken. After the soil was collected, it was brought back to the laboratory for soil particle composition analysis.
[0106] 4. Results of hydraulic erosion in the drawdown zone 1. Wave load analysis results According to the statistical analysis of wave data collected by the RBR wave instrument, the statistical results show that the effective wave height of waves in the waters of each test area ranges from 0.24 to 17.57 cm, with an average value of 1.91 cm and an effective period average of 2.51 s (as shown in Tables 1 and 2). Based on this, it can be concluded that the wave erosion in the field test area is mainly small-scale wave erosion with a long period.
[0107] Table 1 Statistics of measured wave heights at observation points
[0108] Table 2 Observation point measured period statistics
[0109] In addition, the Weibull distribution curve is used to fit the nearshore wave data to obtain the distribution histogram of the nearshore significant wave height, as shown in Fig.10 As shown. Fig.10 A shows that the wave height is mainly concentrated in the range of 0~4 cm, with waves accounting for 90.7% in this wave height range and a peak value of about 2 cm. The analysis results show that the nearshore waves of the reservoir in the restoration test area are small waves with small scale and strong repeatability, which belong to regular waves ( Fig.10 B). This is consistent with the measurements of the Three Gorges waves by other scholars (Fu Xuhui et al., 2020; Li Yu et al., 2016), that is, the wave erosion suffered by the reservoir area in the Three Gorges drawdown zone is mainly small waves, and only the channel slopes and the bank slopes in the dock area will suffer from more serious, discontinuous and irregular wave erosion.
[0110] 2. Erosion analysis results Test area: After the slope of the test area was repaired, it experienced hydraulic erosion for half a year. During the test period, the water level changed from 157.5 to 161 m, with a fluctuation of 3.5 m. An obvious white strip was formed in the area where the water level dropped, and the exposed area of the test area was about half a grid frame. From the perspective of on-site erosion characteristics, the soil in the SJP substrate porous structure on-site test area showed a phenomenon of patchy shedding, and the peeling of the surface soil did not show a significant difference in the upper, middle and lower parts of the grid beam; along the depth, although the hydraulic erosion of the drawdown zone caused the surface soil of the test area to peel off, the surface soil was chiseled open and it was found that the amount of SJP reinforced soil retained in the lower porous structure was good and did not receive obvious erosion.
[0111] Control area: The plants on the slopes in the control area showed obvious differences in distribution. The vegetation in the lower part of the slope grew vigorously, with a coverage of 50-60%, while the vegetation in the upper part of the slope grew sparsely, with a coverage of about 30-40%. Through on-site investigation, it was found that the growth of plants showed an obvious positive correlation with the stock distribution of soil, showing a relationship similar to "skin and hair": that is, the soil stock in the upper part of the slope was small, and the plants lacked the soil matrix required for growth, and the coverage was low; and when the soil particles in the upper part of the slope migrated to the lower part of the slope, the plants grew more luxuriantly due to the rich soil matrix in the lower part of the slope. Further investigation of the area found that the slopes in the control area showed obvious soil particle loss as a whole. There were even holes in some parts. This was because the porous structure on the surface of the hole was sealed. Once the water flow entered, it was difficult to discharge, and it would continue to erode in it, causing the internal soil to be carried away by the water flow and forming water erosion holes or even collapse.
[0112] 5. Distribution characteristics and migration patterns of soil particles In order to further understand the distribution characteristics and migration patterns of soil particles in the experimental and control areas, the soil collected from different parts of the two areas on site was analyzed for particle composition. First, the soil was preliminarily screened to remove gravel and plant roots, and the basic particle size composition of the soil was measured by wet method using a laser particle size analyzer (model LS13320) (3 sets of parallel samples).
[0113] Experimental area: By analyzing the soil particle composition in different parts, such as Fig.11 As shown in the figure, it is found that the d90 of the surface layer, 0~5cm, and 5~10cm decreases successively, indicating that the soil particles are finer as they go inward. The surface soil shows a slight "sanding" phenomenon due to the severe hydraulic erosion in the drawdown zone. This is because the fine particles on the surface are eroded away by the reciprocating wave motion. The hydraulic action suffered by the SJP reinforced soil inside the porous structure of the SJP substrate is more of reservoir water immersion and softening. The d10 of the soil at 5~10cm is 7.86um, which is slightly smaller than the original soil (d10=12.64um), because under the action of static water, the large aggregates formed by the SJP reinforced soil will inevitably disintegrate and break to produce fine particles. However, since the bottom of this area is an impermeable lattice panel and the interior of the repair structure is tortuous and porous, no large infiltration water flow is formed, so the fine soil particles are not taken out.
[0114] Control area: The soil collected from the control area was analyzed for particle composition, such as Fig.12 As shown in the figure, it is found that after the water level of the Three Gorges Reservoir has risen and fallen periodically, the soil particle composition in different parts of the area has changed significantly. From the overall distribution curve of soil particles, it can be seen that the soil particle composition curve in the upper part of the control area frame shows a significant downward trend; and the soil particle distribution curves in the three parts are significantly different.
[0115] The soil particle composition of different parts of the control area was further analyzed, such as Fig.13As shown. The analysis found that the soil particle composition and distribution form in this area are significantly different. The clay and silt content of the upper soil in the control area is less, while the sand content is higher, showing a clear peak form. The peak of the sand part is obvious, indicating that the upper part of the frame suffers from strong hydraulic erosion, and only coarse particles can remain, while fine particles are easily taken away. The soil particle distribution in the middle of the frame is completely different. Although it also shows a peak distribution, the peak of the particle composition shifts to the silt. Because the clay and silt content in this part is high, and the d90 of the surface layer is greater than the d90 of the deep layer, it indicates that there are more fine particles in the surface layer than in the porous interior. There are two main reasons for this: ① Under the action of wave erosion, the fine particles eroded from the upper part of the frame along the slope migrate down with the slope water flow and deposit here; ② The soil particles inside the porous structure move upward along the depth direction. Because the internal structure is porous and permeable, when the reservoir water level drops rapidly, the water level inside the slope in the repair area is temporarily higher than the reservoir water level, forming a water flow that seeps to the outside of the slope, thereby moving the internal soil to the surface. From the soil composition in the lower part of the frame, it can be seen that the tail (fine particles) of the soil particle distribution has increased significantly, because the clay and silt content in this area is higher than that in the middle, indicating that the sedimentation effect at this location is more obvious.
[0116] In summary, through the field test using the porous structure of the SJP substrate, and the comparison analysis of the original repaired slope of Baidicheng, the test results are as follows: (1) By analyzing the wave erosion conditions in the test area, it was found that the effective wave height ranged from 0.24 to 17.57 cm, with an average value of 1.91 cm and an effective period of 2.51 s. This shows that the nearshore waves in the test area did not have the effect of large waves, and were small in scale and highly repeatable.
[0117] (2) Through the analysis of soil erosion characteristics in the experimental area and the control area, it was found that after the water level rise and fall and hydraulic erosion in the drawdown zone, the soil retention effect in the experimental area was better, and only the surface soil fell in patches; while in the control area, after experiencing hydraulic erosion in the drawdown zone, the soil and plant distribution showed obvious stratification from the overall and local characteristics (the upper soil was severely lost and the plant distribution was sparse; while the lower soil was deposited here, and the corresponding plant coverage was better).
[0118] (3) Through stratified sampling and analysis of the soil in the test area and the control area, it was found that after half a year of hydraulic erosion in the drawdown zone, the soil particle composition in the test area was not significantly different from the original soil. Only the loss of fine particles in the surface layer was obvious and the particle composition distribution showed a slight peak distribution. The soil inside the porous structure of the SJP substrate was well preserved and no obvious fine particle migration occurred. The test results show that the porous structure of the SJP substrate can bind soil particles and resist hydraulic erosion in the drawdown zone. This is consistent with the soil erosion characteristics of the area, that is, the surface soil falls in patches while the soil inside the porous structure is well preserved. It is suitable for promotion and application in ecological slope protection in the drawdown zone. The soil particle composition in different parts of the slope frame of the control area is obviously different, changing from the fat tail distribution form in the lower part to the peak form, and the peak value of the particle composition distribution shifts to the coarse particles, indicating that the soil erosion characteristics of the area are upper erosion-middle and lower accumulation. From the comparative analysis results of soil loss patterns and soil erosion characteristics in the two regions, it can be seen that the porous structure of the SJP substrate can significantly improve the soil's anti-erosion ability, and with the support of the porous structure, it can achieve a better soil fixation effect. The use of the SJP substrate porous structure, a new type of composite soil fixation restoration method, can reduce soil matrix loss in the early stage of ecological restoration of the drawdown zone before the vegetation roots grow up, and provide soil matrix and vegetation space for subsequent plant growth.
Claims
1. A SJP substrate porous structure, characterized in that: Made from the following raw materials in weight percentage: Porous structure 51.5%~56.3%; SJP organic solidified soil paste 43.7%~48.5%; The SJP organic solidified soil slurry is made of raw materials containing the following weight percentages: Viscosity time-varying grouting material 1.2%; Soil 74.8%; Water 24.0%; The porous structure is made of raw materials containing the following weight percentages: Volcanic rocks 64.1-68.2%; Cementitious materials 31.5~35.6%; Water reducing agent 0.1~0.6%.
2. A SJP substrate porous structure as claimed in claim 1, characterized in that: Made from the following raw materials in weight percentage: porous structure 54.7%; SJP organically stabilized soil paste 45.3%; The SJP organic solidified soil slurry is made of raw materials containing the following weight percentages: Viscosity time-varying grouting material 1.2%; Soil 74.8%; Water 24.0%; The porous structure is made of raw materials containing the following weight percentages: volcanic rock 66.8%; cementitious materials 32.8%; Water reducing agent 0.4%.
3. A SJP substrate porous structure as claimed in claim 1, characterized in that: The cementitious material is made of raw materials containing the following weight percentages: Portland cement 50.2~54.1%; Fly ash 10.1~14.5%; Water 32.3~37.9%.
4. A SJP substrate porous structure as claimed in claim 3, characterized in that, The silicate cement is silicate cement with a strength grade of P.O42.5, and the fly ash is secondary fly ash; Among them, the loss on ignition of silicate cement is 0.97, and the weight percentage of each oxide in silicate cement is: SiO220.38~22.35%; Fe2O34.47~4.82%; Al2O35.23~5.89%; CaO61.01~63.19%; MgO2.05~2.96%; SO31.55~1.73%; NaO1.02~1.10%.
5. A method for preparing a porous structure of a SJP substrate as claimed in any one of claims 1 to 4, characterized in that: The specific steps are: (1) Preparation of porous structure; (2) Prepare SJP organic solidified soil slurry; (3) The SJP organic solidified soil slurry is poured into the porous structure by vibration molding to obtain the SJP substrate porous structure.
6. The method according to claim 5, characterized in that: The production of the porous structure includes the following steps: (1-1) Pour all the volcanic rocks into a blender and add 45-55% water, stirring to pre-wet the volcanic rocks; (1-2) Add 60-80% of cementitious material and 60-80% of water reducing agent into the mixer and stir until the volcanic rock is completely covered by the adhesive material to form a shell; (1-3) Add the remaining water to the blender and continue blending until the shell becomes thinner and evenly coated; (1-4) Slowly add the remaining cementitious material and water reducing agent into the mixer while stirring; (1-5) After the mixing is completed, the mixed material is poured into a mold and vibrated, and then molded to obtain a porous structure.
7. The method according to claim 5, characterized in that: The porous structure of the SJP substrate obtained in step (3) is subjected to an alkali reduction treatment, and the specific treatment method is as follows: The porous structure of the SJP substrate was immersed in a 2% oxalic acid solution or a 7% FeSO4 solution.
8. An application of the porous SJP substrate structure as described in any one of claims 1 to 4 in ecological slope protection in a drawdown zone.
Citation Information
Patent Citations
Ecological restoration method for water-level-fluctuating zone of reservoir
CN115262469A
Vegetation restoration device suitable for hydro-fluctuation belt of reservoir and production method of vegetation restoration device
CN117099586A
Hydro-fluctuation belt slope protection device and production method thereof
CN117356310A
Cited By
Dry and wet dual-purpose screening device for soil
CN119838880A
Waste residue improvement method based on combination of water retention material and aspergillus niger
CN122477916A